A Comparative Antipyretic Activity of the Crude Extracts of the Ariel Parts of Glycosmis pentaphylla and Bauhinia variegata - Rohit S1, Mandloi A1, Mandal S2*, Upadhyay N1, Sharma I1 (Recent Research in Science and Technology, 2011)
This study indicates that Glycosmis pentaphylla and Bauhinia variegata extracts have good antipyretic activity. Ethanolic extract of Bauhinia variegata and Glycosmis pentaphylla exhibited significant anti-pyretic activities in Brewer’s yeast induced pyrexia in rats. The maximum antipyretic activity throughout the test period of 6 hours was produced by ethanolic extract of plant Glycosmis pentaphylla (200 mg/kg) and standard (paracetamol treated) group. In general, non-steroidal anti-inflammatory drugs produce their antipyretic action through the inhibition of prostaglandin synthetase within the Hypothalamus. Therefore, the antipyretic activity of extracts of Bauhinia variegata and Glycosmis pentaphylla is probably by inhibition of prostaglandin synthesis in hypothalamus.